Emotional Competencies in Higher Education: A Systematic Review - Taza Chambi , Esmeralda (2025)
The objective of this study was to analyze the role of emotional competencies in higher education, evaluating their impact on holistic development, academic success, and the mental health of the community. A descriptive systematic review was conducted using a selective search of high-impact databases, primarily Scopus. The filtering process yielded a final sample of 28 scientific articles published between 2021 and 2025. We focused on articles with practical findings on the interaction between emotional management, mental health, and the effectiveness of educational stakeholders, excluding purely theoretical ones. The results indicate that these skills have evolved from complementary resources to determinants of educational quality. They act as protective factors against stress and foster institutional commitment. The study concludes that integrating these competencies into the curriculum and teacher training is necessary to create resilient academic environments.